Biocontrol of Listeria monocytogenes by lactic acid bacteria isolated from brewer's grains used as feedstuff in Argentina. (March 2015) - Asurmendi, P.; García, M.J.; Pascual, L.; Barberis, L.
Abstract: Brewer's grains are the most important by-product of the brewery industry and it is mostly used as a protein and energy source in animal nutrition. Listeria monocytogenes is a food-borne pathogen can cause invasive diseases such as meningoencephalitis, sepsis, abortion, and gastroenteritis in humans and several animal species. The aim of this work was to study the antilisterial activity of lactic acid bacteria (LAB) isolated from brewer's grains. The incidence of Listeria spp. in brewer's grains was 3.12%. Twenty-one LAB inhibited the growth of the eight strains of L. monocytogenes . The mean inhibition halo of cell free supernatants of LAB ranged between 11.5 and 24.5 mm. The isolation of lactic acid bacteria with antilisterial activity from brewer's grains is promising based on their capacity to produce antimicrobial compounds. The production of antimicrobial metabolites by LAB in the substrate would generate an unfavorable environment for the growth of the pathogenic bacterium under study. Highlights: This is the first report on the isolation of Listeria monocytogenes from brewer's grains. Lactic Acid Bacteria (LAB) isolated from brewer's grains produce bioactive compounds against Listeria sp. The most Cell Free Supernatants (CFS) of LAB maintained the antlisteria activity after neutralized.